المساعدة الطبية على الانجاب بين الفقه الاسلامي و القانون الجزائري - شعبان قرمان; عبدالحميد داي; د/ عمر بن عيشوش (جامعة عمار ثليجي الاغواط, 2024)
ملخصالمذكرة: إنَّ المساعـــدة الطبِّية على الإنجـــاب بين الفقه الإسلامي والقانــــون الجزائري من المواضيع التي لاقت جدلا واسعا , حيث رسمت الشَّريعة الإسلامية وكذا التَّشريعات القـــانونية الحدود الأخلاقية والإنسانية والطبِّية لهذه العملية. فما وافق أحكام الشَّرع والقــانون وكــانت الغـــاية منه العلاج فهو مشروع ويستوجب التَّنظـــيم، ومـــا خالف الفطرة وعرَّض كرامة الإنسان للإهانة فإنَّ هذا حتمًا يحظره الشَّرع ويستوجب المنع. تكمن أهمية هذه الدراسة في * معرفة أهميَّة النَّسَب عند المسلمين، ووجوب المحافظة عليه وصِيَانته مِمَّا يُفْسِدُه أو يُشكِّك فيه، وانتشار ظاهرة الأطفال مجهولي النَّسَب النَّاتِجين عن العلاقات غير الشَرْعِيَة . * بيان أَنَّ الشَّريعة الإسلامية شاملة وصالحة لِكُلِّ زمَانٍ ومكَانٍ وإثبات أَنَّ المسائل المُسْتَجَدَّة في عصر لها حكم في شريعة الله. كما استخلص فقهاء الشَّرِيعة أحكامًا شرعية باعتباره من النَّوازِل الطبِّية، التي استجدَّت في العصر الحَاضِر لعِلاَج العُقم، على عكس المشرِّع الجزائري الذي حصرها في مادَّة وحيدة بالرَّغم من تداعياتها الكبيرة والإشكالات المترتِّبة عنها ذلك لأن طلب العِلاج مشروع للزَّوجين اللذين يُعانيان أحدهُما أو كِلاهُما مِنَ العُقم ، باعتبار ذلك مرضًا يمسُّ أحد أهم أغراض الزَّواج مِنَ النَّاحية الشَّرعية والإسلامية وهو التَّناسل وبقاء الذُّرِيَّة. أجازت الشَّريعة الإسلامية عملية التَّلقيح الاصطناعي بين الزَّوجين وأثناء حياتهما وأقرَّت به ثُبوت النَّسب، وأَنَّ الإنجاب خَارِج نِطَاق الزَّواج يُعتبر باطلاً ولاغيًا ومُحرَّمًا، وهو ما ذهب إليه المشرِّع الجزائري في قانون الأسرة الجزائري, فيما منع اللجوء إلى الأم البديلة (استئجار الأرحام) الكلماتالمفتاحية: المساعدة, الطبية, الإنجاب, الشريعة , القانون . Abstract: Medical assistance in procreation between Islamic jurisprudence and Algerian law is one of the topics that has received widespread controversy, as Islamic law, as well as legal legislation, has drawn the moral, humanitarian and medical limits for this process. Whatever is in accordance with the provisions of Sharia and the law and its purpose is treatment is legitimate and requires regulation, and whatever violates common sense and exposes human dignity to insult, this is inevitably prohibited by Sharia and requires prohibition. The importance of this study lies in * knowing the importance of lineage among Muslims, the necessity of preserving it and preserving it from anything that corrupts or calls into question, and the spread of the phenomenon of children of unknown parentage resulting from illegitimate relationships. * A statement that Islamic law is comprehensive and valid for every time and place and proof that emerging issues in an era have a ruling in God’s law. Sharia jurists have also drawn legal rulings as it is one of the medical issues that have emerged in the present era to treat infertility, in contrast to the Algerian legislator who limited it to a single article despite its great repercussions and the resulting problems. This is because requesting treatment is legitimate for a couple in which one or both of them suffer from infertility, considering This is a disease that affects one of the most important purposes of marriage from a legal and Islamic perspective, which is reproduction and the survival of offspring. Islamic law has permitted the process of artificial insemination between spouses and during their lives and has recognized the proof of paternity, and that procreation outside marriage is considered null and void and forbidden, which is what the Algerian legislator stated in the Algerian Family Code, while prohibiting resorting to surrogate mothers (surrogacy). Keywords: Assistance, medical, procreation, Sharia, law.